Pelatihan Kewirausahaan Digital dalam Meningkatkan Keterampilan Bisnis Mahasiswa - Mardani Eka Ningrum; Sri Mulyeni; Mita Puspita; Aida Fitriani; Marzuki Marzuki (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This community service program aims to strengthen students' business skills through digital-based entrepreneurship training. The initiative responds to rapid technological development, requiring students to develop adaptive skills for building businesses in the digital realm to compete globally. Activities were designed using a participatory approach encompassing four stages: planning, training implementation, mentoring, and evaluation. The training combined material delivery, interactive discussions, case analysis, and hands-on practice based on the learning by doing principle, with practical sessions focused on creating digital business accounts and developing online marketing strategies. Results indicate a significant improvement in participants' knowledge and skills in digital entrepreneurship, as reflected in pre- and post-training evaluation scores and participants' ability to apply the learned material. The program also positively impacted students' motivation, creativity, and confidence in starting digital businesses. Throughout the activities, participants demonstrated active involvement and high enthusiasm, ultimately producing a simple business plan as a final achievement. Overall, this program contributes meaningfully to improving students' business competencies while fostering an independent and innovative entrepreneurial mindset. Continuous follow-up through mentoring programs and advanced training is recommended to ensure the benefits obtained can develop optimally.